EXPLORING THE INFLUENCE OF PROMOTION, POSITIVE EMOTION, AND PSYCHOLOGICAL DISTANCE TO ONLINE IMPULSIVE BUYING BEHAVIOR IN INDONESIA - Bimo Wibisono, Ario
Technology based era has brought market into higher level competition, online shopping has set the new standard for customer-marketer transaction. The amount of user that relies shopping using online methods has significantly increased around the world. Prior study held in developed country has resulted variety of customers online shopping motives, as an emerging country where online transaction amount starts to significantly increase, marketer’s challenges in Indonesia is to acknowledge the driven factors of Indonesian online impulsive buying behavior. The model of this study was constructed by reflecting to how people implemented their personality traits, hedonic browsing behavior (HDBW) and utilitarian browsing behavior (UTBW) and motivates them to make an online impulsive buying (IMPB) decision. There are a lot of factors that could influence online impulsive buying behavior, however this study has constructed the models based on prior study related to online impulsive buying in several countries and proposed promotion (PMTN), positive emotion (PSTE), and psychological distance (PSYD) as variable predictors. This study validated the framework of online impulsive buying behavior in Indonesia using quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM). The finding shows that positive emotion (PSTE) and promotion (PMTN) could trigger customers hedonic browsing behavior (HDBW) and help marketers drive customers online impulsive buying behavior (IMPB), however both positive emotion (PSTE) and promotion (PMTN) are not directly affecting online impulsive buying behavior (IMPB). This result contradicted with psychological distance (PSYD) factor which directly affecting online impulsive buying behavior (IMPB), but utilitarian browsing behavior (UTBW) found to be weakly mediates it, thus it could be concluded that it is not necessary to mediates psychological distance (PSYD) using utilitarian browsing behavior (UTBW) to online impulsive buying behavior (IMPB). Result implicates that Indonesian customers are dominated with impulsive yet efficient-first type of customers, thus the strategy that combines both their hedonic browsing behavior and utilitarian browsing behavior, is most likely to success in Indonesia.